Quasi-solid-state agar-based polymer electrolytes for dye-sensitized solar cell applications using imidazolium-based ionic liquid - Nadia, S.R.; Khanmirzaei, M.H.; Ramesh, S.; Ramesh, K. (Springer Verlag, 2017)
Agar as a natural polymer is used to prepare quasi-solid-state polymer electrolytes (QSPEs). Two different iodide salts namely sodium iodide (NaI) and potassium iodide (KI) are incorporated. To enhance the ionic conductivity of the QSPE system, 1-methyl-3-propylimidazolium iodide (MPII) ionic liquid is added. The highest ionic conductivity of 1.48 × 10−3 S cm−1 was achieved after addition of 50 wt.% of KI and 3.0 g of MPII ionic liquid. QSPEs are studied for temperature-dependent ionic conductivity behavior. QSPEs are studied for structural properties using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The structural studies revealed that the complexation between agar polymer, iodide salts, and MPII ionic liquid has occurred. QSPEs are sandwiched between counter and working electrodes to fabricated DSSC and analyzed under sun simulator. The highest efficiency of 2.16% is achieved with incorporation of 3.0 g MPII ionic liquid.